Time-Dependent Efficiency of Free Trade Agreements: The Case of Slovenia and the CEFTA Agreement - Joze P. Damijan; Igor Masten (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2002)
In international trade literature, there is a common feature that the abolishment of barriers to trade leads to the expansion of trade flows. Most of the empirical studies aiming at simulation of welfare effects of trade liberalization explicitly make use of this direct tariff reduction - trade expansion mechanism. The present paper, on the contrary, explores the time-dependent efficiency of free trade agreements (FTAs) in a panel framework using static and dynamic model specifications. It shows that trade liberalization per se needs time to become efficient and that immediately after the enforcement of the FTA, the autonomous factors (such as domestic demand for particular import goods) are of great importance, since they may or may not stimulate expansion of bilateral trade flows. Using an illustrative case of rapid expansion of Slovenian imports from other Central and Eastern European countries (CEECs) in the period 1993?998, the paper demonstrates that tariff reductions become effective in the second to third year after enforcement of the FTA. In addition, it is shown that there is a non-linear relationship between tariff reductions and trade expansions since new business connections have to be established.
Keywords: F13; F14; F15; 330; Trade Liberalization; Efficiency of Free-Trade Agreements; Außenhandelsliberalisierung; Freihandelszone; Außenhandelseffekt; Dauer; Slowenien